Gratitude and positive parent-child relationship on Filipino adolescents with depression - Badillo, Maranela L. (Animo Repository, 2017)
The present study aims to describe gratitude, parent-child relationship, and both gratitude and parent-child relationship in the context of depression based from the perspectives of Filipino parents and adolescents. Interviews were conducted with 12 participants which consisted of an adolescent who has been previously diagnosed and is now cleared from clinical depression, and their respective parent with a total of 6 pairs. Adolescents were first screened with the Beck's Depression Inventory (BDI) to check if they were in good mental health to be interviewed-- all were reported to be fit for the interview. After the interview phase, it was found with the use of thematic analysis that there is gratitude between parents and adolescents despite the adolescents' depression. Positive parent-child relationship also contributed to better coping of the adolescents to depression as well as the development of gratitude and vice versa between the parents and adolescents.